Cover Picture: Encapsulation of Isolated Luminophores within Supramolecular Cages (Angew. Chem. Int. Ed. 45/2017). Issue 45 (11th October 2017) - Handke, Marcel; Adachi, Takuji; Hu, Chunhua; Ward, Michael D.
Abstract : Organic solid‐state dye lasers promise versatility with respect to spectral tuning, but often face challenges owing to self‐quenching by aggregation. In their Communication onpage 14003 ff., M. D. Ward et al. describe an approach to solid‐state lasing compounds in which isolated luminescent guest molecules, a range of well‐known laser dyes, are encapsulated in cages of a crystalline hydrogen‐bonded zeolite‐like framework. The luminescence of each compound is consistent with the absence of self‐quenching, and the emission color can be tuned from blue to red by the choice of guest molecule.